Remote Back Strain: A Strategy for Modulating the Reactivity of Triarylboranes - Sakuraba, Mahiro; Morishita, Taichi; Hashimoto, Taiki; Ogoshi, Sensuke; Hoshimoto, Yoichi (Synlett, 2023)
A strategy for modulating the Lewis acidity of triarylboranes is proposed based on the concept of remote back strain. Steric repulsion and noncovalent interactions, both generated between the aryl meta-substituents of triarylboranes, are found to be critical for determining the strength of the remote back strain. Applying this concept, we synthesized B[2,6-F2-3,5-(TMS)2-C6H]3 and the liquid B[2,6-F2-3,5-(allyl)2-C6H]3 and we demonstrated their superior catalytic activity for the hydrogenation of quinoline relative to B(C6F5)3 or B(2,6-F2C6H3)3. Moreover, we established the first example of the catalytic hydrogenation of quinoline by using B[2,6-F2-3,5-(allyl)2-C6H]3 in the presence of a gaseous 1:1:1 molar mixture of H2, CO, and CO2.
Keywords: triarylboranes; Lewis acids; frustrated Lewis pairs; hydrogenation; boron catalysis; hydrogen separation